Item analysis of life skills achievement test for Nigerian non- formal education learners: implications for the Millennium Development Goal(MDGs) (2006)
One of the major challenges faced by developing nations is the high rate of illiteracy. Nigeria, in a bid to check the problem, adopts both the formal and non- formal education approaches. In order to ascertain the quality of the non-formal approach, item analysis of one of the subjects being taught in the literacy centres is examined in this study. A multi-stage sampling design was used to select 2,326 post-literacy learners in the 36 states and the FCT, Abuja. The sample is made up of 1,021 (43.9 percent) urban centres and 1,309 (56.1 percent) rural centres, 46 percent were male and 54 were female learners. An achievement test containing 55 items in life skill was used to collect data. Item analysis was done using difficulty indices; discrimination indices; inter-correlation matrix and reliability of the test. The results show that only 16.37% of the items have zero and negative discrimination indices while the rest are positive. Above 21.82% and 18.18% of the items are difficult and easy respectively and majority of the items are good. Examples of some difficult items are disscussed. implication of the study is also discussed.